Antimicrobial and Hemostatic Diatom Biosilica Composite Sponge - Sol Youn; Mi-Ran Ki; Ki Ha Min; Mohamed A. A. Abdelhamid; Seung Pil Pack (MDPI AG, 2024)
The 3D nanopatterned silica shells of diatoms have gained attention as drug delivery vehicles because of their high porosity, extensive surface area, and compatibility with living organisms. Tooth extraction may result in various complications, including impaired blood clotting, desiccation of the root canal, and infection. Therapeutic sponges that possess multiple properties, such as the ability to stop bleeding and kill bacteria, provide numerous advantages for the healing of the area where a tooth has been removed. This study involved the fabrication of a composite material with antibacterial and hemostatic properties for dental extraction sponges. We achieved this by utilizing the porous nature and hemostatic capabilities of diatom biosilica. The antibiotic used was doxycycline. The gelatin-based diatom biosilica composite with antibiotics had the ability to prevent bleeding and release the antibiotic over a longer time compared to gelatin sponge. These properties indicate its potential as a highly promising medical device for facilitating rapid healing following tooth extraction.